Foundations of woodworking - Pekovich, Michael (The Taunton, Press, 2021)
"Foundations of Woodworking gets to the very core of the craft of woodworking: laying out, cutting, and assembling joinery for furniture and other treasured wood objects. After an introductory chapter on the basic woodworking strategies that apply to anything you might build, Pekovich dives into a step-by-step, project-by-project description of the essential wood joints, from rabbets and dadoes through mortise and tenons to dovetails and miters. Master these joints--with a combination of hand tools and power tools--and the door is open to create just about any design you can think of"--